2020
DOI: 10.1039/d0dt01389g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cobalt(iii)–phenylalanine complexes for hypoxia-activated drug delivery

Abstract: Four cobalt(III)-phenylalanine complexes, [Co(Phe)(py2en)](ClO4)2·H2O (1), [Co(Phe)(TPA)](ClO4)2·H2O (2), [Co(Phe)(py2enMe2)](ClO4)2·H2O (3) and [Co(bipy)2(Phe)](ClO4)2·H2O (4), were investigated as prototype models for hypoxia-activated delivery of melphalan - a phenylalanine derivative anticancer drug of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…The same group has reported another paper where Co(III) complexes under hypoxic condition have been tested for delivery of melphalan – which is a derivative of phenylalanine and nitrogen mustard class of anticancer drug [109] . They have synthesised and characterised four cobalt(III)‐phenylalanine complexes, [Co(Phe)(py 2 en)](ClO 4 ) 2 ⋅ H 2 O ( 34 ), [Co(Phe)(TPA)](ClO 4 ) 2 ⋅ H 2 O ( 35 ), [Co(Phe)(py 2 enMe 2 )](ClO4) 2 ⋅ H 2 O ( 36 ) and [Co(bipy) 2 (Phe)](ClO 4 ) 2 ⋅ H 2 O ( 37 ) (Figure 9).…”
Section: Co(iii) Based Hypoxic Activated Prodrugmentioning
confidence: 99%
“…The same group has reported another paper where Co(III) complexes under hypoxic condition have been tested for delivery of melphalan – which is a derivative of phenylalanine and nitrogen mustard class of anticancer drug [109] . They have synthesised and characterised four cobalt(III)‐phenylalanine complexes, [Co(Phe)(py 2 en)](ClO 4 ) 2 ⋅ H 2 O ( 34 ), [Co(Phe)(TPA)](ClO 4 ) 2 ⋅ H 2 O ( 35 ), [Co(Phe)(py 2 enMe 2 )](ClO4) 2 ⋅ H 2 O ( 36 ) and [Co(bipy) 2 (Phe)](ClO 4 ) 2 ⋅ H 2 O ( 37 ) (Figure 9).…”
Section: Co(iii) Based Hypoxic Activated Prodrugmentioning
confidence: 99%
“…34,42,43 Interestingly, for most cobalt(III) prodrugs reported in literature irreversible redox processes in aqueous solutions could be observed, which contradicts this hypothesis. [44][45][46][47] Notably, pulse radiolysis studies of cobalt(III) nitrogen mustard complexes indeed suggested that the re-oxidation rate under normoxia is too slow and the cobalt(III) complexes rather compete with molecular oxygen for one-electron reductants. 48 Nevertheless, different cobalt(III) complexes with irreversible electrochemical behavior exhibited strong hypoxiadependent activity against cancer cells in vitro and in vivo, proving the potential of such complexes.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…31 (iii) Compared to platinum and ruthenium in the same group, it has the advantage of being inexpensive and easily accessible. 32 Recently, biological functional studies on several compounds containing Co 2+ have already been carried out. A series of Co( ii ) complexes of terpyridine, such as [Co(L) 2 ](ClO 4 ) 2 , have been synthesized by Sovan Roy et al , 33 and their photocytotoxicity and cellular uptake properties have been studied.…”
Section: Introductionmentioning
confidence: 99%